2019
DOI: 10.1038/s41388-019-0953-9
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of the transcriptional kinase CDK7 overcomes therapeutic resistance in HER2-positive breast cancers

Abstract: Resistance of breast cancer to human epidermal growth factor receptor 2 (HER2) inhibitors involves reprogramming of the kinome through HER2/HER3 signaling via the activation of multiple tyrosine kinases and transcriptional upregulation. The heterogeneity of induced kinases prevents kinase targeting by a single kinase inhibitor and presents a major challenge to the treatment of therapeutically recalcitrant HER2-positive breast cancers (HER2+ BCs). As a result, there is a critical need for effective treatment th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 52 publications
(65 reference statements)
3
48
0
Order By: Relevance
“…These results suggest that combining CDK7 and EGFR inhibitors may be a novel therapeutic approach for the treatment of breast cancer. In agreement with previous reports, THZ1 significantly inhibited the phosphorylation of RNA Pol II C-terminal domain at S2, S5 and S7 in a dose-dependent manner in all cell lines [2,9,17,18,26], confirming functional CDK7 inhibition. However, the magnitude of THZ1-induced decreases in Pol II phosphorylation did not correlate with THZ1 sensitivity.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results suggest that combining CDK7 and EGFR inhibitors may be a novel therapeutic approach for the treatment of breast cancer. In agreement with previous reports, THZ1 significantly inhibited the phosphorylation of RNA Pol II C-terminal domain at S2, S5 and S7 in a dose-dependent manner in all cell lines [2,9,17,18,26], confirming functional CDK7 inhibition. However, the magnitude of THZ1-induced decreases in Pol II phosphorylation did not correlate with THZ1 sensitivity.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous reports [18], we found a strong positive correlation between high CDK7 expression and worse relapse free survival in TNBC. However, we also found strong positive correlations between CDK7 RNA expression and survival in both luminal B (rapidly growing ER+) and HER2+ breast cancer patients, the HER2+ findings consistent with a recent report [17]. In contrast to negative prognostic correlations of CDK7 RNA levels, a study that used immunohistochemistry- Having found that many of the genes inhibited by THZ1 are regulated in an EGF-dependent manner, we hypothesized that inhibition of CDK7-mediated transcription via THZ1 could potentiate the effects of EGFR inhibition in breast cancer.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…CDK7 inhibitors combined with tamoxifen reduced the expression level of cyclin D1 and E1 which were reported to be associated with tamoxifen resistance [35,36]. Also, CDK7's role in overcoming chemotherapeutic resistance in breast cancer was mentioned before, where CDK7 inhibition by TZH1 was found to reverse the resistant in HER2+ breast cancer patients [37]. Moreover, CDK7 inhibition increased tamoxifen-induced apoptosis in vitro and In vivo models compared to inhibitor or tamoxifen individually.…”
Section: Discussionmentioning
confidence: 92%